Obesogenic diet induces circuit-specific memory deficits in mice - Ioannis Bakoyiannis; Eva Gunnel Ducourneau; Mateo N'diaye; Alice Fermigier; Celine Ducroix-Crepy; Clementine Bosch-Bouju; Etienne Coutureau; Pierre Trifilieff; Guillaume Ferreira (eLife, 2024)
Obesity is associated with neurocognitive dysfunction, including memory deficits. This is particularly worrisome when obesity occurs during adolescence, a maturational period for brain structures critical for cognition. In rodent models, we recently reported that memory impairments induced by obesogenic high-fat diet (HFD) intake during the periadolescent period can be reversed by chemogenetic manipulation of the ventral hippocampus (vHPC). Here, we used an intersectional viral approach in HFD-fed male mice to chemogenetically inactivate specific vHPC efferent pathways to nucleus accumbens (NAc) or medial prefrontal cortex (mPFC) during memory tasks. We first demonstrated that HFD enhanced activation of both pathways after training and that our chemogenetic approach was effective in normalizing this activation. Inactivation of the vHPC–NAc pathway rescued HFD-induced deficits in recognition but not location memory. Conversely, inactivation of the vHPC–mPFC pathway restored location but not recognition memory impairments produced by HFD. Either pathway manipulation did not affect exploration or anxiety-like behaviour. These findings suggest that HFD intake throughout adolescence impairs different types of memory through overactivation of specific hippocampal efferent pathways and that targeting these overactive pathways has therapeutic potential.